2001
DOI: 10.1080/08941930152024200
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lazaroid U-74389G on Pulmonary Ischemia - Reperfusion Injury in Dogs

Abstract: Lipid peroxidation induced by oxygen free radicals is a contributing factor in ischemia-reperfusion injury. Lazaroid U-74389G (LAZ-G) is a group of new synthetic 21-aminosteroids and inhibits irondependent lipid peroxidation. We investigated the effects of LAZ-G on pulmonary ischemia-reperfusion injury in dogs. Twenty dogs were divided into three groups. In the LAZ-G group (n = 6), LAZ-G was administered 15 min before ischemia. In the St group (n = 5), methylprednisolone was injected 15 min before ischemia and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Allopurinol (xanthine oxidase inhibitor), SOD, catalase, deferoxamine (iron chelator), dimethylthiourea (28), or NAC (both thiols) prevented reperfusion injury of the lungs (2, 67,73). Lazaroid, which inhibits iron-dependent lipid peroxidation, also inhibits lung I/R injury in a canine model (141). Antioxidants may also be beneficial to diminish graft rejection after lung transplantation (17).…”
Section: Antioxidant and Lung Injurymentioning
confidence: 98%
“…Allopurinol (xanthine oxidase inhibitor), SOD, catalase, deferoxamine (iron chelator), dimethylthiourea (28), or NAC (both thiols) prevented reperfusion injury of the lungs (2, 67,73). Lazaroid, which inhibits iron-dependent lipid peroxidation, also inhibits lung I/R injury in a canine model (141). Antioxidants may also be beneficial to diminish graft rejection after lung transplantation (17).…”
Section: Antioxidant and Lung Injurymentioning
confidence: 98%
“…Moreover, when released into the circulation, iron can activate platelet aggregation. An experimental model of lung IR injury using 3 hours of warm ischemia in dogs showed that a new type of lazaroid is able to reduce iron-dependent lipid peroxidation [ 75 ].…”
Section: Ironmentioning
confidence: 99%
“…It has been documented previously that lazaroids minimize ischemic/reperfusion injury to the lungs (45)(46)(47)(48). Tonoue et al (46) demonstrated that the PaO 2 and PaCO 2 from the lazaroid-treated group were significantly better than control in lung preservation.…”
Section: Discussionmentioning
confidence: 95%